Perceptions of the tutor teachers on the pedagogical and professional competence of pre-service teacher professional education in University of Islam Malang - Abidin, Zainal; Setiawan, Yayan Eryk; Zauri, Ahmad Sufyan; Murniatie, Itsnaniyah Umie (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
One of the problems faced by student teachers is the low level of pedagogical and professional competence. To overcome this problem, one must find out the teacher's perception of these two competencies. Therefore, this research aims to analyze pre-service teachers' perceptions regarding the pedagogical and professional competence of students in the pre-service teacher professional education study program at the Islamic University of Malang. This type of research is quantitative research with a survey approach. This research population was conducted in 66 schools. The research sample consisted of 120 civil service teachers who assessed Teacher Professional Education (PPG) students who carried out practical learning activities. This research instrument is a questionnaire to determine the teacher's perception of students' pedagogical and professional competence, consisting of 64 valid and reliable statements. The results of filling out the questionnaire were analyzed by determining the average. The research results show that the average teacher's perception of prospective teacher students' pedagogical and professional competence is 4.61 and 4.66, which means very good. It is concluded that prospective teacher students have excellent pedagogical and professional competencies for each study program in Teacher Professional Education. Apart from that, the implications of the results of this research can be used by lecturers to improve professional and pedagogical competency indicators, which, on average, are still low through classroom learning.